Positive Youth Development based on 5Cs and 7Cs in Physical Education: A Literature Review (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2025)
Positive Youth Development, in the context of Physical Education, is an approach that prioritizes youth empowerment through physical activity and sports. Through physical activity intervened with a deliberately designed 5Cs and 7Cs program, youth can acquire motor skills, knowledge about health and fitness, and social skills needed for interacting with others. There is limited extensive research that specifically discusses PYD based on the 5Cs and 7Cs model in Physical Education. This article emphasizes the need for a more comprehensive analysis that explores the relationship between PYD and Physical Education implementing the 5Cs and 7Cs model. This study aimed to provide practical insights into how Physical Education can be designed and implemented to support positive youth development. By connecting theoretical studies with practical applications, it offers educators a framework for fostering resilience and positive development in students, which is currently limited in previous research. This study used the Systematic Literature Review method by reviewing Scopus-indexed international journals published in the last 10 years. The results of the study showed that research data in the 2012-2022 period experienced fluctuations. In 2021, the research trend was at its highest peak (14 articles), while the lowest research trend was in 2013 (1 article). It showed that the researcher interest in this topic could be more stable. The findings of the search results on this topic had not been extensively carried out. Only four research results and one chapter of a research book could be identified. Several research results used qualitative research methods (two articles) and survey methods (two articles). The authors did not find research using quantitative research methods on the 5Cs and 7Cs models, especially in Physical Education.